Perinatal Pet Exposure, Faecal Microbiota, and Wheezy Bronchitis: Is There a Connection?. (9th January 2013) - Nermes, Merja; Niinivirta, Katri; Nylund, Lotta; Laitinen, Kirsi; Matomäki, Jaakko; Salminen, Seppo; Isolauri, Erika
Abstract : Background . The hygiene hypothesis suggests that high hygiene standards have led to an immune dysfunction and an increase in allergic diseases. Farming-related exposures are associated with a decreased risk of asthma. Since the gut microbiota may be a pivotal component in the hygiene hypothesis, we studied whether perinatal exposure to pets, doctor's diagnosed wheezy bronchitis (WB), and compositional changes in the gut microbiota are interrelated among urban infants. Methods . Data were collected prospectively from a mother-infant nutrition study. Data on perinatal pet ownership, WB, and the microbiota composition of faecal samples of the infants assessed by quantitative PCR at 1 month were compared. Results . None of the 30 infants exposed to pets had suffered from WB by 24 months, whereas 15 of the 99 (15%) nonexposed infants had had WB (P = 0.03 ). The counts of Bifidobacterium longum were higher in samples (n = 17 ) from nonwheezing infants with pet exposure compared to those (n = 10 ) in wheezing infants without pet exposure (8.59/10.44 versus 5.94/9.86, resp. (median/upper limit of range, bacteria(log)/g of stool); P = 0.02 ). B. breve was more abundant in the wheezing infants (P = 0.02 ).